2006
DOI: 10.1038/sj.ki.5000383
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of local dipyridamole therapy in a porcine model of arteriovenous graft stenosis

Abstract: Perivascular delivery of antiproliferative drugs has been proposed as an approach to prevent neointimal hyperplasia associated with hemodialysis polytetrafluoroethylene (PTFE) grafts. We examined this approach to deliver dipyridamole in a porcine graft model. PTFE grafts were implanted between the carotid artery and external jugular vein bilaterally in pigs. During the surgery or 1 week post-graft placement, dipyridamole (0.26-52 mg) alone or incorporated in microspheres was mixed with an injectable polymeric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 22 publications
2
22
1
Order By: Relevance
“…Consistent with this hypothesis, a recent study in swine showed that direct application of dipyridamole to the periadventitial surface of the graft-vein anastomosis in a concentration that inhibits vascular smooth muscle proliferation in vitro failed to prevent the development of neointimal hyperplasia. 15 Whether the combination of ERDP/ASA is better than aspirin for hemodialysis graft patency remains uncertain. Two large trials in patients with cerebrovascular disease have shown that ERDP/ASA is more effective than aspirin alone for secondary prevention of stroke or vascular death.…”
Section: Clinical Research Wwwjasnorgmentioning
confidence: 99%
“…Consistent with this hypothesis, a recent study in swine showed that direct application of dipyridamole to the periadventitial surface of the graft-vein anastomosis in a concentration that inhibits vascular smooth muscle proliferation in vitro failed to prevent the development of neointimal hyperplasia. 15 Whether the combination of ERDP/ASA is better than aspirin for hemodialysis graft patency remains uncertain. Two large trials in patients with cerebrovascular disease have shown that ERDP/ASA is more effective than aspirin alone for secondary prevention of stroke or vascular death.…”
Section: Clinical Research Wwwjasnorgmentioning
confidence: 99%
“…This indicates that acute decompensation may gradually transition to residual renal compensation, indicating an improved simulation of chronic renal insufficiency 28 days after surgery. It is currently considered that the important pathological changes of intimal hyperplasia are the increase of vascular smooth muscle cells and extracellular matrix (13,(25)(26)(27)(28). The present study showed that there was intimal hyperplasia of the fistula in the first week after surgery, and the pathological features included smooth muscle cell proliferation, the accumulation of collagen fibers, extensive polypoidal hyperplasia, and evident stenosis in the fourth week after surgery.…”
Section: Daymentioning
confidence: 57%
“…The addition of polymeric microspheres to the thermosensitive triblock polymer was necessary in order to prolong the drug release, because of the relative hydrophilicity of dipyridamole [26]. There was no significant difference in neointima formation between this intervention and untreated graft [27]. This lack of efficacy may be due to a low potency of dipyridamole to inhibit the proliferation of myofibroblasts and VSMC in vivo, or the suboptimal release profile of the hydrophilic drug.…”
Section: Local Sustained Drug Deliverymentioning
confidence: 80%